SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BLT MENGGUNAKAN METODE MULTY ATTRIBUTE UTILITY THEORY - siti aminah; asrul abdullah; istikoma istikoma (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
In this research, a decision support system for accepting direct cash assistance (BLT) has been built using the Multi Attribute Utility Theory (MAUT) method. The system built is website-based. The purpose of this study is to be able to provide results for beneficiaries based on the criteria determined by the village using the MAUT method. The criteria used are extreme poverty, chronic or chronic illness, elderly or not working, disabled or within the family. Tests in this study used 39 alternative data. This data is compared with the results of manual calculations in excel. The results obtained from this study indicate that the value of the alternative Mr. Yohanes Ibu has the highest weight, namely 1. Based on these figures, it may be inferred that computations performed manually and utilizing a system provide identical results. In order to ensure that the system constructed adheres to the MAUT calculation approach, it is necessary to convert various interests into numerical values on a scale of 0-1. Here, 0 represents the lowest value and 1 represents the highest value.